An Evaluation of the IOLMaster 700. Issue 2 (March 2019) - Bullimore, Mark A.; Slade, Stephen; Yoo, Paul; Otani, Todd
Abstract : Objectives: To evaluate the repeatability and reproducibility of the Carl Zeiss Meditec IOLMaster 700, which uses swept-source optical coherence tomography technology, along with its agreement with the IOLMaster 500 and Lenstar LS 900. Methods: In a clinical practice, complete measurements were taken on one eye of 100 subjects: 51 with cataracts and 49 with clear lenses. Three sets of measurements were taken by 3 operators with three different IOLMaster 700 units, and one operator took 3 measurements with the IOLMaster 500 and the Lenstar. A random-effects model of analysis of variance was used to estimate the repeatability and reproducibility. The 95% limits of agreement (95% LoA) were calculated for all comparisons. Results: Comparing the IOLMaster 700 and IOLMaster 500 in cataract patients, 95% LoA were −0.01 to +0.06 mm for axial length, −0.44 to +0.27 D for corneal power, and −0.18 to +0.17 mm for anterior chamber depth. Comparing the IOLMaster 700 and Lenstar for corneal thickness and lens thickness yielded 95% LoA of −4 to +13 μm and −0.26 to +0.41 mm, respectively. The repeatability and reproducibility limits for the IOLMaster 700 were ±0.014 and ±0.023 mm for axial length; ±0.26 and ±0.27 D for corneal power; ±7 and ±11 μm for corneal thickness; ±0.02 and ±0.02 mm for anterior chamber depth; and ±0.02 and ±0.05 mm for lens thickness, respectively. Conclusions: There was good agreement between the IOLMaster 700 and comparator instruments and superior or equivalent precision. Some differences were noted, but not considered clinically meaningful.